Intangible Investment and Human Resources. The New WIFO Taxonomy of Manufacturing Industries - Michael Peneder (Austrian Institute of Economic Research (WIFO), 1999)
Statistical cluster techniques are applied in the development of two new taxonomies of manufacturing industries. The first focuses on the distinction between exogenous, location dependent comparative cost advantages, such as the relative abundance of capital or labour, and endogenously created firm specific advantages resulting from intangible investments in marketing or innovation. The second taxonomy discriminates between industries according to their employment of skilled labour. Finally, econometric tests are used to investigate the presumed complementarity between intangible investments and human resources.
Keywords: L1; L6; M3; O3; 330; Intangible investments; human resources; endogenous sunk costs; industry structure; statistical cluster analysis; Industrie; Clusteranalyse; Immaterielle Werte; Humanressourcen; Theorie